Influence of Externally Bonded CFRP on the Shear Behavior of Strengthened and Rehabilitated Reinforced Concrete T-Beams Containing Shear Stirrups - Mu’tasime Abdel-Jaber (Fibers, 2021)
This study aims to investigate the effect of using externally bonded carbon fiber reinforced polymer (CFRP) on the strengthening and rehabilitation of reinforced concrete (RC) T-beams reinforced with steel stirrups. Three configurations of CFRP were used: 45° inclined strips, horizontal straight strips, and U-wrapped sheets. A total of 19 specimens of strengthened and preloaded RC T-beams were experimentally tested. The experimental results were compared with the theoretical values determined according to the ACI 440.2R−17 code. The results proved that all beams containing CFRP recorded higher strength than the control sample, regardless of whether the beams were tested for strengthening or rehabilitation purposes. The horizontal straight strips of the CFRP schemes recorded the highest enhancement in the shear capacity, followed by the U-wrapped sheets and inclined strips. Moreover, the ACI 440.2R−17 code overestimated the capacities of some samples.